Rocks and minerals - Discovery Channel School; Discovery Communications Inc. ([Bethesda, Md.] : Discovery Communications Inc., 2003)
This cd-rom describes minerals, summarizes the rock cycle, describes the work of geologists, featured the geologic record of the Grand Canyon, traces the development of the Yosemite Valley and its granite walls, describes geologic forces that create jade and jadeite and painstaking process
Teacher's guide in PDF and Microsoft Word format
System requirements : Windows 95/98, pentium processor 100 MHz and above, 16 MB installed RAM, minimum 25 MB free hard disc space, minimum resolution of 640 X 480, 16-bit color, 4 X CD-ROM drive
System requirements : Power PC macintoch at 100 MHz or better, running system 7.6.1 or higher, minimum of 8 Mb available RAM, minimum of 25 MB free had disc space, 640 X 480 resolutions, 16-bit color, 4 X multimedia-compliant CD-ROM drive
Keywords: Rocks -- Juvenile literature; Minerals -- Juvenile literature; Rocks; Minerals